Techno-functional, antioxidants, microstructural, and sensory characteristics of biscuits as affected by fat replacer using roasted and germinated chickpea (Cicer arietinum L.) - Syed Muhammad Ghufran Saeed; Syed Arsalan Ali; Javeria Naz; Manahil Mirza; Manal Fawzy Elkhadragy; Hany Mohamed Yehia; Angelo Maria Giuffrè (International Journal of Food Properties)
Obesity is one of the major causes of non-communicable diseases (NCDs) associated with a dietary pattern rich in saturated fat. The present study utilized roasted and germinated chickpeas (Cicer arietinum) flour (RCPF and GCPF) as a replacement for fat in biscuits, known to have nutraceutical properties. The fat content was modified using the following ratios: 10%, 20%, and 30% (w/w) of RCPF/GCPF. Based on the physicochemical analysis, increased concentrations of RCPF and GCPF in the flour blends resulted in higher levels of protein, ash, and crude fiber contents. GCPF was found to contain higher levels of protein (20.20%), ash (4.86%), and crude fiber (3.64%) compared to RCPF. Increased RCPF and GCPF levels resulted in reduction of gluten content, which indicated weak gluten network. Scanning electron micrographs (SEM) of biscuit samples further supported these observations. The farinograph properties showed significant increase (P<0.05) in water absorption and dough development time. Furthermore, when RCPF and GCPF were added to flour blends and biscuits samples, significant increase (P<0.05) in antioxidant activity, total phenolic content, and total flavonoid content was observed. These trends were observed to be more prominent with higher quantities of RCPF and GCPF. Notably, the antioxidant properties of chickpeas were found to be significantly improved (P<0.05) by the process of germination compared to roasting. Moreover, improvements in antioxidant activity might be caused by the increased levels of phenolic compounds and ascorbic acid due to the actions of endogenous hydrolytic enzymes during germination. The dimensional, textural, and sensory properties indicated that RCPF 20% and GCPF 10% can effectively serve as an organic fat substitute in bakery products with enhanced concentrations of proteins, fibers, antioxidants, and bioactive compounds with nutraceutical properties.